2018
DOI: 10.2147/cmar.s161248
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and colorectal cancer risk in the Middle East: gene polymorphisms and expression

Abstract: BackgroundIL-17 expressed by Th17 cells play a crucial role in tissue inflammation by induction of proinflammatory and neutrophil mobilizing cytokines, and IL-17 polymorphisms are associated with colorectal cancer (CRC).ObjectiveWe investigated the expression of IL-17 and the association of IL-17 gene polymorphisms with CRC susceptibility in a Middle East population.Materials and methodsThe study included 117 diagnosed CRC patients and 100 age- and gender-matched healthy controls. IL-17A rs2275913 (G197A) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Thus, the overall effect of IL17 is apparently linked to the localization of IL17-producing cells. A further complication in the definition of the pro-tumor properties of IL17 comes from the IL17A polymorphism rs2275913 (G197A), with the AG and AA genotypes strongly associated to an increased CRC incidence (187191).…”
Section: Nk Cells In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Thus, the overall effect of IL17 is apparently linked to the localization of IL17-producing cells. A further complication in the definition of the pro-tumor properties of IL17 comes from the IL17A polymorphism rs2275913 (G197A), with the AG and AA genotypes strongly associated to an increased CRC incidence (187191).…”
Section: Nk Cells In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Recently, several studies investigated the association between IL-17A rs2275913 polymorphism and risk of CRC [9,11,13–15]. Omrane et al firstly conducted a population-based study to explore the association of rs2275913 polymorphism with CRC risk in a Tunisian population involving 102 CRC patients and 139 controls [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant association with CRC risk was observed for rs2275913 polymorphism in another Tunisian study conducted by Bedoui et al [15]. Additionally, two Caucasian studies also investigated the effect of this SNP on the risk of CRC [9,13]. Nemati et al revealed that AG genotype showed a significantly elevated risk for CRC compared to GG genotype in the Iranian population [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations